Penerapan Model Kooperatif Tipe Team Games Tournament (TGT) Untuk Meningkatkan Pemahaman Konsep Matematis Pada Operasi Hitung Pecahan Siswa Kelas III Sekolah Dasar - Nydia Nur Sendy; Nano Sukmana; Iwan Gunawan (EDUCARE, 2019)
This research is entitled "Application of Team Games Tournament Cooperative Model Type to Increase Understanding of Mathematical Concepts in Fractional Calculating Operations of Class III Elementary Students". This study aims, whether the Cooperative Model Team Games Tournament model can improve the concept understanding in students who learn fraction counting operations in thrity grade and whether the ability to comprehend mathematical concepts in operating materials to calculate fractions of students studying with Team Games Tournament is better than students who study with conventional models. This study uses the theory of Shoimin (2014). The research method used in this study is the quantative approach. The population in this study were all third grade students of Lengkong Besar SDN 0. This study of Data were collected by tests and observation sheets. The results of this study showed that there was an increase in conceptual comprehension in students who studied fractional counting operations in class with the method TGT.